REPRODUCTION OF THREE COLOUR VARIETIES OF ANGELFISH (Pterophyllum scalare) - Darti Satyani (Research Center for Fisheries, 1999)
A study into the reproductive performance of three color varieties of angelfish , Pterophyllum scolore (Black, Black & White, and Marble) was conducted in a farmer's hatchery at Depok, West Java